2000
DOI: 10.1258/1357633001935662
|View full text |Cite
|
Sign up to set email alerts
|

Web-based education and support for patients on the cardiac surgery waiting list

Abstract: We assessed the effectiveness of two methods of patient education, a printed manual and a Website, provided to patients waiting for cardiac surgery. The four-phase study was conducted over two and a half years, and included urban and rural subjects in Vancouver and the interior of British Columbia. The Website was based on the specially developed patient education manual. A pilot evaluation study was carried out to assess the features of the Website and to ensure it was 'user-friendly', after which it was revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…The nurse could detect and take care of problems and, when needed, mediate contact to various other specialists. A previous study showed that nurse-led web-based education and support through e-mail was useful to patients waiting for heart surgery [22], and another study highlighted the advantages of a web-based patient information system for patients waiting for cardiac surgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…The nurse could detect and take care of problems and, when needed, mediate contact to various other specialists. A previous study showed that nurse-led web-based education and support through e-mail was useful to patients waiting for heart surgery [22], and another study highlighted the advantages of a web-based patient information system for patients waiting for cardiac surgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…14,17,18 Although there is no conclusive evidence of online education's overall superiority versus traditional teaching tools, such as books or pamphlets, studies of cardiac populations 19 as well as other medical populations [20][21][22] suggest they are, at the very least, equally effective. Further, Brug et al 8 suggest that computerized education is more readily adaptable to the individual and his or her needs than paper formats.…”
Section: Providing Patient Educationmentioning
confidence: 99%
“…11,12 For patients already diagnosed with cardiovascular disease, WBIs have been shown to increase patient knowledge, independence, self-management, compliance, and quality of life. 13,14 However, the number of Web-based studies to improve psychosocial outcomes in patients with cardiac disease is small. Therefore, more research is needed to refine interventions to the particular needs of subpopulations with cardiac disease and to fully validate their usefulness and efficacy.…”
mentioning
confidence: 99%
“…The Internet makes possible immediate access to and acquisition of encyclopedic information. In the field of cardiac surgery, for example, several authors have described and discussed the use of the Internet for educating cardiac surgery patients on-line [3,4,5,6]. However, little evidence is available about whether and to what extent this patient population actually uses the Internet.…”
Section: Introductionmentioning
confidence: 99%